Waqf as an Islamic Endowment: A Solution for Improving Educational Attainment in Northern Nigerian Communities - Muhammad, Adamu Abubakar; Ardo, Adam Muhammad Ardo; Aliyu, Shafa’at Ahmad; Muhammad, Zuwaira Jibril (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
About 6 out of 10 pupils in Northern Nigerian rural areas are left behind in educational attainment due to poverty, lack of parental support, insecurity challenges, or cultural disparity. This study aims to describe the relationship between socioeconomic status and educational goals in Northern Nigeria and how using and revitalizing Waqf institutions might advance education in the region. Because of socioeconomic factors like poverty, cultural norms, and underfunded educational systems, Northern Nigeria faces significant challenges that impede access to high-quality education and educational goals despite numerous government initiatives. A review of the literature, case studies, and expert interviews are all part of the qualitative technique used in this study. These techniques make it possible to fully comprehend the difficulties the local educational system faces and the historical and contemporary contributions of Waqf institutions to the advancement of education in northern Nigerian communities. Examining pertinent theoretical frameworks and empirical research yields important insights into how Islamic endowment systems can lessen notable educational gaps in the region, which is one of the significant findings of the current research. It also revealed that Waqf models that have worked well in other Muslim countries draw attention to the potential applications for more benefits and to finance education for underprivileged students. Ultimately, the study recommends that including Waqf in educational financing would provide practical, long-term methods to improve educational objectives in the area and lessen the detrimental effects of the socioeconomic crisis.